Integrated nanophotonic devices - Zalevsky, Zeev (William Andrew ; Elsevier Science [distributor], 2010)
Nanophotonics is a field of science and technology based on the manipulation of light with equally miniscule structures, in the same way that computer chips are used to route and switch electrical signals. By enabling new high bandwidth, high speed optoelectronic components, nanophotonics has the potential to revolutionize the fields of telecommunications, computation and sensing. In this book, Zalevsky and Abdulhalim explore one of the key technologies emerging within nanophotonics, that of nano-integrated photonic modulation devices and sensors. The attempt to integrate photonic dynamic devices with microelectronic circuits is becoming a major scientific as well as industrial trend due to the fact that currently processing is mainly achieved using microelectronic chips but transmission, especially for long distances, takes place via optical links. Unlocks the technologies that will turn the rapidly growing research area of nanophotonics into a major area of commercial development, with applications in telecommunications, computing, security and sensing. Nano-integrated photonic modulation devices and sensors are the components that will see nanophotonics moving out of the lab into a new generation of products and services. By covering the scientific fundamentals alongside technological applications, the authors open up this important multidisciplinary subject to readers from a range of scientific backgrounds.
Keywords: Nanophotonics.; elektronické knihy; electronic books